Molecular docking with SARS-CoV-2 and potential drug property of a bioactive novel Zn(II) polymer: A combined experimental and theoretical study. (15th March 2023) - Nashre-ul-Islam, Swah Mohd.; Borah, Kamala Kanta; Raza, Muhammad Asam; Öztürkkan, Füreya Elif
Graphical abstract: Synthesis, characterization and crystal structure of a novel Zn(II) coordination polymer involving CH⋯HC interactions. The polymer gives satisfactory docking results with SARS-CoV-2. Its pharmacokinetic and toxicokinetic properties were evaluated by ADMET calculations. Highlights: A novel Zn(II) polymer involving bridging o -phthalato ligand is synthesized and characterized by single X-ray diffraction and vibrational spectroscopy. The crystal structure is mainly stabilized by CH⋯HC interactions, which finally results in a lattice water enclathrated 3D architecture. Important non-covalent interactions are studied by Hirshfeld surface analysis and other theoretical tools. Molecular docking study carried out with six important proteins of SARS-CoV-2 shows satisfactory results. Docking scores with two of them are even better than those for common antiviral drugs. ADMET calculations support its candidature as a drug molecule. Abstract: A new Zn(II) coordination polymer based on o -phthalato (Phth) and 2-aminopyridine (2-Ampy) viz. {[Zn(2 - Ampy)2 (Phth)]∙(H2 O)]}n (1 ) has been synthesized at room temperature and characterized by elemental analyses, electronic spectroscopy, FT - IR spectroscopy, thermal analysis (TGA/DSC), powder X - ray diffraction (PXRD) and single crystal X - ray diffraction. The basic trimeric units of 1 form a polymeric chain by NH⋯O and π⋯π interactions. These polymeric chains interconnect through various non-covalent interactions in two perpendicular directions to ultimately give rise to a 3D architecture of 1 . The interesting non-covalent interactions in 1, contributing to its stability in the solid state are studied by Hirshfeld surface analysis and other different theoretical tools. Molecular docking study of 1 is performed against six different proteins of SARS-CoV-2. The drug potential of the synthesized compound is evaluated by ADMET calculations.